Answer the attachment
Attachments:
![](https://hi-static.z-dn.net/files/ddf/d05db719fd86afe83a54d0535e668327.jpg)
Answers
Answered by
0
Given equation can be simplified as:-
2(x+y)=3(y+1)
2x+2y=3y+1
2x-y=1
So, the equation takes this form.
When x=-3/2,
Equation is:-
2*-3/2-y=1
-3-y=1
-y=4
y=-4
The graph of the equation 2x-y=1 is attached.
Attachments:
![](https://hi-static.z-dn.net/files/d08/8f500ad966e3e80d77480a96e733e8db.jpg)
Answered by
0
here is your answer with proper steps, hope this helps
Attachments:
![](https://hi-static.z-dn.net/files/db4/db5b9577aa4f74caba0083b2354b12ea.jpg)
arzoo48:
Thxx
Similar questions